Activation of IL1 signaling molecules by Kaposi’s sarcoma-associated herpesvirus - Chen, Jungang; Song, Jiao; James, Jennifer; Plaisance-Bonstaff, Karlie; Post, Steven R.; Qin, Zhiqiang; Dai, Lu (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Kaposi’s Sarcoma-associated Herpesvirus (KSHV) is the etiologic agent of several human cancers, including Kaposi’s sarcoma (KS) and Primary effusion lymphoma (PEL), which are usually seen in immunocompromised patients while lack of effective therapeutic options. Interleukin1 (IL1) family is a major mediator for inflammation response and has functional role in both innate and adaptive immunity. In contrast to the well-studied IL1 molecules, the activation and functional role of IL1 receptor/co-receptor and other related ligands, such as the IL1 receptor accessory protein (IL1RAP), in KSHV pathogenesis and tumorigenesis remain almost unknown. Methods In the current study, a series of KSHV negative and positive primary or tumor cells, as well as AIDS-KS tumor samples from cohort HIV+ patients were used to compare and determine the activation status of IL1 signaling molecules, and their functional roles in KSHV pathogenesis. Results We reported the high activation of multiple IL1 signaling molecules, including IL1, IL36, IL1R1, IL1RAP and IRAKs, during KSHV latent and lytic stages, as well as in clinical samples from patients with KSHV-related malignancies. Directly targeting these molecules especially IL1R1 and IL1RAP significantly impaired the survival and growth of KSHV+ tumor cells, as well as their colony formation on 3-D culture. Conclusion Our data indicate the importance of IL1 signaling molecules in KSHV pathogenesis and tumorigenesis, which may represent attractive therapeutic targets against these virus-associated diseases.